2022
DOI: 10.1515/cclm-2022-0263
|View full text |Cite
|
Sign up to set email alerts
|

Results of a SARS-CoV-2 virus genome detection external quality assessment round focusing on sensitivity of assays and pooling of samples

Abstract: Objectives Results of earlier external quality assessment (EQA) rounds suggested remarkable differences in the sensitivity of SARS-CoV PCR assays. Although the test systems are intended to detect SARS-CoV-2 in individual samples, screening is often applied to sample pools to increase efficiency and decrease costs. However, it is unknown to what extent these tests actually meet the manufacturer’s specifications for sensitivity and how they perform when testing sample pools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…We and others have observed through EQAs that there exists relatively high variability when reporting Ct values, and we presume this is also true outside of ring trials, for example, when measuring virus concentration in patient samples [5,8,9,11,12,19,21]. Our data suggested that converting Ct values to copies per mL (and reporting them as IU/mL) statistically improved precision for all samples.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We and others have observed through EQAs that there exists relatively high variability when reporting Ct values, and we presume this is also true outside of ring trials, for example, when measuring virus concentration in patient samples [5,8,9,11,12,19,21]. Our data suggested that converting Ct values to copies per mL (and reporting them as IU/mL) statistically improved precision for all samples.…”
Section: Discussionsupporting
confidence: 59%
“…Characterization also included determination of copy number by digital PCR (dPCR). Details of the second round were presented elsewhere [21].…”
Section: Data Collection and Organization Of The Eqasmentioning
confidence: 99%
“…A mathematical model for the extent of the (relative) loss of sensitivity has been published earlier [52,53]. The expected loss of relative sensitivity was evident in the EQA round that reported on this [24]. Such information can only be obtained through a speci cally designed EQA round and needs collaboration of the participant test facility.…”
Section: Discussionmentioning
confidence: 88%
“…Literature on EQA is generally rare. We identi ed a total of 17 publications on EQA of SARS-CoV-2 in PubMed with the search terms "EQA" or "external quality assessment" or "pro ciency testing" or "PT" and "SARS-CoV-2" or "Covid-19" (search performed July 2022, period searched 01/2020 to 07/2022, see Table 1) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Information from each publication was aggregated (Table 1) and the subject criteria were derived from this.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation